Stakeholder-designed scenarios for global food security assessments - van Dijk, Michiel; Gramberger, Marc; Laborde Debucquet, David; Mandryk, Maryia; Shutes, Lindsay; Stehfest, Elke; Valin, Hugo; Faradsch, Katharina (Elsevier, 2020)
To guide policymaking, decision makers require a good understanding of the long-term drivers of food security and their interactions. Scenario analysis is widely considered as the appropriate tool to assess ‘wicked problems’, such as ensuring global food security, that are characterized by a high level of complexity and uncertainty. This paper describes the development process, storylines and drivers of four new global scenarios that are specifically designed to explore global food security up to the year 2050. To ensure the relevance, credibility and legitimacy of the scenarios, they have been developed using a participatory process, involving a diverse group of stakeholders. The scenarios consist of storylines and a scenario database that presents projections for key drivers, which can be used as an input into global simulation models.